Kemudahan dari Allah: Ringkasan Tafsir Ibnu Katsir - Muhammad Nasib Ar_Rifa'i (Gema Insani Press, 1999)
ast, jil.1 =c.1; sn,jl.1,c.2/oen, jil.1=c.3/tr, jil.3=c.1/nr, jil.1,c.4; jil.2,c.1; jil.3,c.2; jil.4,c.1/irh, jil.1,c.5-6, jil2,c.2-3, jil.3,c.3-4/jil.4,c.2-3